أثر استخدام التعلم الإلكتروني في مادة التربية الإسلامية على دافعية الطلبة دراسة من وجهة نظر المعلمين بأبو ظبي- الإمارات العربية المتحدة.: The Effect of Using E-Learning in Islamic Education on Student’ Motivation: A Study from The Perspective of Teachers in Abu Dhabi - Alsafadi, Alaa; Jamil, Asyraf Isyraqi (Journal Al-Muqaddimah, 2023)
This research primarily aims to investigate the impact of utilizing e-learning in Islamic Education on students’ motivation and academic competence from the perspective of teachers in Abu Dhabi، United Arab Emirates. This main objective is further explored through three sub-questions، seeking to reveal the influence of e-learning on students’ motivation and academic competence in learning Islamic Education. To achieve the research objectives، the study focused on the population of Islamic Education teachers in private schools in Abu Dhabi، amounting to 438 teachers in 198 schools. A random sample of 200 teachers was selected for the research. The research employed a suitable descriptive survey methodology given the nature of the study. Research tools included the development of a questionnaire to collect data، along with assessing its psychometric properties. After collecting and statistically analysing the research data، the results indicated a significant impact of e-learning on students’ motivation and academic competence in Islamic Education. Based on the research findings, the study recommends several key actions. These include the necessity of integrating e-learning in the teaching of Islamic Education، as well as providing training for teachers and students on the skills required for effective utilization of e-learning methods and strategies.